2002
DOI: 10.1142/s0219199702000725
|View full text |Cite
|
Sign up to set email alerts
|

Non-Radial Ground States for the Hénon Equation

Abstract: We analyse symmetry breaking for ground states of the Hénon equation [7] in a ball. Asymptotic estimates of the transition are also given when p is close to either 2 or 2 * .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
173
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(185 citation statements)
references
References 11 publications
10
173
0
2
Order By: Relevance
“…So it can be expected that problem (1.2) possesses non-radial solutions. Such solutions were found in [13] for 2 < p < 2n n−2 and in [12] for p = 2n n−2 . Furthermore, it was proved in [4] that the maximum point of the ground state solution u p of (1.2) approaches a boundary point of ∂Ω as p → 2 * .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…So it can be expected that problem (1.2) possesses non-radial solutions. Such solutions were found in [13] for 2 < p < 2n n−2 and in [12] for p = 2n n−2 . Furthermore, it was proved in [4] that the maximum point of the ground state solution u p of (1.2) approaches a boundary point of ∂Ω as p → 2 * .…”
Section: Introductionmentioning
confidence: 82%
“…Such a problem has been extensively studied, see for instance [4,11,12] and [13] etc. Interesting phenomenon concerning problem (1.2) that was revealed recently includes, among other things, that the exponent α affects the critical exponent for the existence of solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing some ideas and some results from [9], we also prove existence of non radial solutions for a range of growth of f including supercritical growth. We will find the solutions as minima on the Nehari manifold of the functional usually associated to (1). So the main points of the present paper can be summarized as follows: non homogeneous nonlinearity, supercritical growth, Nehari manifold.…”
Section: Introductionmentioning
confidence: 99%
“…In the case in which f (t) is a power, say f (t) = |t| p−2 t, the problem is known as Hénon's equation (see [10]). A seminal paper of Smets, Su and Willem [1] showed that, for large α's, there is a breaking of symmetry and a new, non radial, solution appears. After that, much work has been made to study these non radial solutions: multiplicity, shape, asymptotic behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation